Exposure to unpredictability and mental health: Validation of the brief version of the Questionnaire of Unpredictability in Childhood (QUIC-5) in English and Spanish - Lindert, Natasha G.; Maxwell, Megan Y.; Liu, Sabrina R.; Stern, Hal S.; Baram, Tallie Z.; Poggi Davis, Elysia; Risbrough, Victoria B.; Baker, Dewleen G.; Nievergelt, Caroline M.; Glynn, Laura M. (Frontiers in Psychology, 2022)
Unpredictability is increasingly recognized as a primary dimension of early life adversity affecting lifespan mental health trajectories; screening for these experiences is therefore vital. The Questionnaire of Unpredictability in Childhood (QUIC) is a 38-item tool that measures unpredictability in childhood in social, emotional and physical domains. The available evidence indicates that exposure to unpredictable experiences measured with the QUIC predicts internalizing symptoms including depression, anxiety, and anhedonia. The purpose of the present study was to validate English and Spanish brief versions (QUIC-5) suitable for administration in time-limited settings (e.g., clinical care settings, large-scale epidemiological studies). Five representative items were identified from the QUIC and their psychometric properties examined. The predictive validity of the QUIC-5 was then compared to the QUIC by examining mental health in four cohorts: 1) English-speaking adult women (N=116), 2) English-speaking male veterans (N=95), 3) English-speaking male and female adolescents (N=155), and 4) Spanish-speaking male and female adults (N=285). The QUIC-5 demonstrated substantial variance in distributions in each of the cohorts and is correlated on average .84 (r’s =.81-.87) with the full 38-item version. Furthermore, the QUIC-5 predicted internalizing symptoms (anxiety and depression) in all cohorts with similar effect sizes (r’s =.16-.39; all p’s<.05) to the full versions (r’s =.19-.42; all p’s<.05). In sum, the QUIC-5 exhibits good psychometric properties and is a valid alternative to the full QUIC. These findings support the future use of the QUIC-5 in clinical and research settings as a concise way to measure unpredictability, identify risk of psychopathology, and intervene accordingly.